The non-tidal, navigable Thames: a bank erosion management strategy - Reed, Sue (1999)
Processes and mechanisms of bank erosion on the non-tidal, navigable River Thames were identified and investigated using site specific monitoring and extensive geomorphic surveys. As a lowland, impounded river the Thames has little potential for bank erosion associated with reach-scale morphological channel adjustments. In fact, erosion is closely related to local conditions at the bank and significant processes and mechanisms include fluvial entrainment, slumping, and weakening and weathering of in situ bank material. Approximately 38.5km of eroding bankline was measured (-10% of the total length). Average rates of bank erosion monitored ranged from 0.05ni/yr to -0.5m/yr. The relative contribution to bank retreat of each process or mechanism depends on local conditions such as the use of the bank, the type of bank material and the bank geometry and the type of vegetation. Analysis of the causes of bank retreat at 147 sites along the River Thames revealed that erosion was generally influenced by a combination of factors. Navigation related activities contribute to the bank erosion at nearly all sites (-90%) but is solely responsible for erosion at only about 12%. Factors related to the use of the bank and adjacent land contribute to erosion along -65% of the total length of eroding bank but are the sole influence at only -5%. Channel planform and geometry contribute to -53% of observed bank erosion, but are the sole influence at less than <1% of the erosion sites. A review of selected of erosion control techniques applied on the River Thames suggested that solutions tend to be over-engineered and that strategies adopted were not necessarily appropriate for the causes and consequences of the bank erosion. Furthermore, whilst mitigation measures are often incorporated into the solutions, environmental enhancements are rarely included. Assessment of the causes and consequences of erosion has led to the development of a bank erosion management strategy for the River Thames based on geomorphological and sustainability principles. The strategy is presented as a transferable tool through which to achieve sustainable river management.